Anteseden Penggunaan E-Filing Dan Dampaknya Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pada Daerah Istimewa Yogyakarta - Effendi, Abdul Baasith; Hidayatulloh, Amir (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2020)
As a bureaucracy that manages a source of state revenue, the Directorate-General of Taxes is required to continually improve services in the tax sector, one of which is by utilizing information technology through the use of e-filing. This study aims to analyze the factors that encourage taxpayers to use e-filing and its impact on taxpayer compliance. The population of this study is an individual taxpayer who is in the Special Region of Yogyakarta. The sampling technique in this study used purposive sampling, with the criteria (1) individual taxpayers who are in the Special Region of Yogyakarta, (2) individual taxpayers who have a Taxpayer Identification Number, and (3) individual taxpayers who use e-filing. Collecting data in this study using a questionnaire given directly to respondents. Respondents in this study amounted to 98 respondents. The data analysis technique in this study used Partial Least Square with the help of the SmartPLS tool. This study shows that the use of e-filing is influenced by the perception of ease of use and social factors. Meanwhile, perceived usefulness has no effect on the use of e-filing. Finally, the use of e-filing can affect individual taxpayer compliance.